2019
DOI: 10.1159/000506123
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Knowledge and Attitudes of the General Public among the Bangladeshi Community in England: A Focus Group Study

Abstract: Background: Increasing life expectancy worldwide means more people will develop dementia. Despite the rapid growth in older Bangladeshi immigrants living in the UK, there is little evidence of how community members understand and view the process of ageing and dementia. However, Bangladeshis have a higher risk of developing type 2 diabetes and heart disease, both of which are important indicators of dementia development in old age. This study aimed to explore and analyse the perception and knowledge of, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Unlike previous studies conducted among South Asian communities, a striking theme has emerged from research regarding stigma among the Bangladeshi community in the UK. 8,9,15,16,26 There was no evidence for stigma, which was consistent with a study on attitudes in an African American community in the USA, which found no stigma related with dementia 27 . Signs and symptoms of dementia such as memory loss, confusion, inappropriate behavior, problems with communication, faulty reasoning, hallucination, fainting, and agitation usually escalate stigma among other South Asian communities.…”
Section: Revivalist Islam In Tackling Stigmasupporting
confidence: 75%
See 4 more Smart Citations
“…Unlike previous studies conducted among South Asian communities, a striking theme has emerged from research regarding stigma among the Bangladeshi community in the UK. 8,9,15,16,26 There was no evidence for stigma, which was consistent with a study on attitudes in an African American community in the USA, which found no stigma related with dementia 27 . Signs and symptoms of dementia such as memory loss, confusion, inappropriate behavior, problems with communication, faulty reasoning, hallucination, fainting, and agitation usually escalate stigma among other South Asian communities.…”
Section: Revivalist Islam In Tackling Stigmasupporting
confidence: 75%
“…South Asian caregivers provide higher levels of care than any other group in England and Bangladeshi caregivers deliver levels of care three times higher than the overall UK population 13 . Bangladeshi family caregivers are a largely hidden and forgotten group who do not identify themselves as caregivers, but classify themselves as family members 14‐16 …”
Section: Bangladeshi Caregiversmentioning
confidence: 99%
See 3 more Smart Citations